Immunotherapy in colorectal cancer: Statuses and strategies - Yuan Li; Zewei Cheng; Shengli Li; Jiwei Zhang (Heliyon)
Colorectal cancer (CRC) is widely recognized as the third most prevalent malignancy globally and the second leading cause of cancer-related mortality. Traditional treatment modalities for CRC, including surgery, chemotherapy, and radiotherapy, can be utilized either individually or in combination. However, these treatments frequently result in significant side effects due to their non-specificity and cytotoxicity affecting all cells. Moreover, a considerable number of patients face relapses following these treatments. Consequently, it is imperative to explore more efficacious treatment interventions for CRC patients. Immunotherapy, an emerging frontier in oncology, represents a novel therapeutic approach that leverages the body's immune system to target cancer cells. The principal advantage of immunotherapy is its capacity to selectively target cancer cells while minimizing damage to healthy cells. Its recent adoption as a neoadjuvant therapy presents significant potential to transform the treatment landscape for both primary resectable and metastatic CRC. This review endeavors to offer a comprehensive overview of current strategies in CRC immunotherapy, critically analyze existing literature, underscore anticipated outcomes from ongoing clinical trials, and deliberate on the challenges and impediments encountered within the field of immunotherapy.